OPTIMALISASI PERAN STRATEGIS AMIL ZAKAT DALAM PERSPEKTIF HUKUM ISLAM DAN HUKUM POSITIF INDONESIA - Ahmad Mukri Aji (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2014)
Abstract: Optimizing the Strategic Role of Zakat in the Perspective of Islamic Law and the Positive Law in Indonesia. Zakat is a part of the religious pillars that must be enforced. It is an important component that has a vertical and horizontal dimension of worship in order to maintain the benefit of human life. Zakat has a particularly significant role in maintaining the stability of the economy. Hence require good management, it is recommended in the Qur'an as Amilin. The Amilin is expected to mediate professionally and seriously to take care of, manage, collect, and distribute zakat. In this paper, zakat is expected to play an optimal role in order to empower the existing charity. So it can contribute to the welfare of mankind. Keywords: Optimizing, Strategic Role, The Amil of Zakat Abstrak: Optimalisasi Peran Strategis Amil Zakat Dalam Perspektif Hukum Islam dan Hukum Positif Indonesia. Zakat merupakan bagian dari pilar agama yang harus ditegakkan. Ia merupakan komponen penting yang memiliki dimensi ibadah vertikal dan horizontal guna menjaga kemaslahatan hidup manusia. Zakat memiliki peran yang signifikan terutama dalam menjaga kestabilan perekonomian. Karenanya diperlukan manajemen pengelolaan yang baik, yang dalam hal ini direkomendasikan Alquran dengan sebutan amilin. Pihak ini diharapkan mampu memediasi secara profesional dan serius untuk mengurus, memanage, mengumpulkan, dan mendistribusikan zakat. Dalam tulisan ini, amil zakat diharapkan berperan secara optimal guna memberdayakan zakat yang ada. Sehingga dapat memberikan sumbangsih kesejahteraan bagi umat manusia. Kata kunci: Optimalisasi, Peran Strategis, Amil ZakatDOI:10.15408/sjsbs.v1i1.1523